(untitled) (Global Journal of Human-Social Science, 2015)
Poverty alleviation has become an important issue for a developing country like Bangladesh. Considering the importance, the study aims to identify and suggest some approaches of poverty alleviation from Islamic perspective. In order to attain the objective of the study, the descriptive method of analysis was adopted. The main causes of poverty in Bangladesh are: corruption, injustice, poor ethics of work, lack of monitoring and follow up in implementing the poverty alleviation programs. It is found from the analysis that moral education, modification of land or agricultural rules, restructuring labor policy, facilitating access to credit for the poor. In addition, the study suggests that executing Zakah system properly, and reducing wastage and extravagancy in spending money are the two important approaches advocated by Islam to alleviate poverty from Bangladesh.